Authors (The Biblical archaeology review, 2021)
Yonatan Adler ("Watertight and Rock Solid,") is Senior Lecturer in Archaeology at Ariel University in Israel. His research focuses on Jewish ritual practices as evidenced in the archaeological record. He has directed excavations of chalk vessel workshops at ‘Einot Amitai and Reina.